Електронні засоби дослідження механічних властивостей біологічних тканин - Dubko, Andrii; Osipov, Roman; Bondarenko, Yuliia; Bondarenko, Oleksandr (PE "Politekhperiodika", Book and Journal Publishers, 2020)
The paper shows the relevance of studying the mechanical properties of biological tissues and biocompatible materials for solving the problems of general and reconstructive surgery, transplantology, manual therapy, virtual simulation of surgical operations, robotic surgery, etc. The authors present basic information about biological tissue as an object of research and give a brief overview of the devices used for studying the mechanical characteristics of biological tissues. An experimental system for testing deformations of biological tissues and biocompatible materials during compression is described. The system is developed using modern hardware and software, as well as effective technical solutions. The results of the practical use of the developed device are presented and the obtained dependences of the mechanical stress of biological tissue samples on their deformation under pressure are analyzed. The system has high metrological characteristics and low cost, and allows performing all the necessary functions for measuring, processing and visualizing the data. The measurements obtained with this system can help form the recommendations for doctors on choosing the optimal operation mode of medical devices and instruments in each specific case. In addition, the measured data can be used to create mathematical models of biological tissues and biocompatible materials in order to further carry out virtual experiments. In further studies, the authors plan to create the mathematical models of biological tissues based on the finite element method and using the actual values characterizing the tissue, obtained with the developed system.